Tantangan dan Solusi pada Penerapan Tujuh Kebiasaan Anak Indonesia Hebat - Saifuddin, Saifuddin; Syukri, Nabawi (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study examines the challenges and solutions in implementing the seven habits of great Indonesian children through a literature review. Using a library research method, the findings reveal several key issues. First, challenges include limited awareness among teachers, parents, and students regarding the importance of these habits; excessive use of gadgets influenced by technology and social media; unsupportive family environments; inadequate supporting facilities; and entrenched cultural practices that hinder change. Second, effective solutions emphasize collaborative efforts among schools, families, and communities through continuous education, communication, regular evaluation, and mentoring. The study also highlights the importance of adopting active, participatory, and interactive learning methods, promoting role models among teachers, parents, and community leaders, and integrating character education into school curricula. Furthermore, guiding children toward responsible and wise use of technology is considered essential. In conclusion, strengthening cooperation between educational institutions, families, and communities, supported by character-based education and technological literacy, is crucial for successfully instilling the seven habits in Indonesian children. This study provides practical recommendations that may serve as a reference for policymakers, educators, and parents to foster stronger character development in the younger generation.